Application of the Problem Based Learning Model with the Assistance of Audio Visual Media in Improving Mathematics Learning on Whole Number Addition and Subtraction Material for Grade 3 Students of UPTD SDN 37 Barru - J, Sri Wiwiyanti; Hidayat, Taufiq; Wahyuni, Andi Ardhil; Arman, Arman (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2025)
This research uses a Classroom Action Research (PTK) approach which is carried out collaboratively. This research aims to determine the improvement in student learning outcomes in mathematics subjects regarding Whole Numbers in class III through the application of the Problem Based Learning (PBL) learning model. The subjects of this research were 12 students in class III at UPTD SDN 37 Barru, with a composition of 4 female students and 8 male students. The type of research is classroom action research with two cycles. Each cycle consists of planning, implementation, observation and reflection. Data collection techniques and tools in this research use descriptive analysis techniques for data in the form of student work documents, score lists and observation sheets. The results of this research show that using the Problem Based Learning (PBL) Learning Model can be a fun learning variation for students so that proven to improve student learning outcomes in Class III at UPTD SDN 37 Barru. After using the Problem Based Learning (PBL) learning model, students' learning outcomes only reached an average score of 81.66, then there was an increase after continuing in cycle 2, namely 86.25%. Therefore, the application of the Problem Based Learning (PBL) learning model can improve mathematics learning outcomes in whole number material.